Heavy metals in hair samples: a pilot study of anaemic children in Kazakhstan, Kyrgyzstan and Uzbekistan - Brázdová, Zuzana; Pomerleau, Joceline; Fiala, Jindřich; Vorlová, Lenka; Müllerová, Dana (Central European Journal of Public Health, 2014)
BACKGROUND: Heavy metals with their potential haematotoxic effect can contribute to the risks of anaemia in children in the Central Asian Republics (CAR), where burden and exposure to these metals is still not sufficiently known and reported. METHODS: Cross-sectional study was performed in Central Asian countries in hospitals in Kazakhstan, Kyrgyzstan and Uzbekistan with the aim to investigate the potential contribution of heavy metals to anaemia in children. In each country, 20 children were recruited, all were hospitalised with diagnosed anaemia. A sample of hair was taken from each child to assess the hair concentration of lead, cadmium and mercury. RESULTS: Relatively high levels of hair lead were observed, particularly in Kyrgyzstan. While lead and cadmium concentrations did not differ significantly among countries, mercury was lower in Kazakhstan than in Kyrgyzstan (p < 0.05) and Uzbekistan (p < 0.001). Hair lead and cadmium levels were significantly positively correlated (correlation coefficient = 0.51, p < 0.001). CONCLUSION: The results of this study showed higher than expected levels of hair lead, cadmium and mercury in anaemic children. Because iron deficiency anaemia is a major public health problem in CAR, further investigation of the extent of exposure to heavy metal and its contribution in iron deficiency anaemia in the region would be recommended.
Keywords: Hair; Female; olovo; předškolní dítě; dítě; kadmium; Asia, Central; vlasy, chlupy; ženské pohlaví; průřezové studie; Cadmium; Adolescent; střední Asie; rtuť; lidé; anemie z nedostatku železa; Pilot Projects; pilotní projekty; Lead; Anemia, Iron-Deficiency; Mercury; Cross-Sectional Studies; Male; Hemoglobins; těžké kovy; Environmental Pollutants; Child, Preschool; vystavení vlivu životního prostředí; hemoglobiny; Child; mužské pohlaví; látky znečišťující životní prostředí; Environmental Exposure; Metals, Heavy; mladiství; Humans